Therapeutic Modulation of Brain Temperature: Relevance of Hypothermia to Inflammatory Changes following Transient Cerebral Ischemia in Rats (Bangladesh Journal of Neuroscience, 2013)
Background : In stroke, the ischemic crisis activates a series of events, including the inflammatory reactions that are potentiated by reperfusion, eventually leading to neuronal damage. Mild hypothermia has been considered to have a protective effect during ischemic neuronal cell death. The chief aim in this study was to investigate whether changing temperature during and after ischemia could minimize this damage by reducing the inflammatory injury.Material and Methods: The effect of moderate whole body hypothermia (300 C) on transient focal cerebral ischemia induced inflammatory injury was investigated. Experimental stroke (transient focal cerebral ischemia) was induced by a 2-hour middle cerebral artery occlusion (MCAO) with the use of a suture inserting into the lumen of the internal carotid artery (ICA) in male Wistar rats. Histopathological evaluation was performed 96 h after reperfusion.Results: MCAO induced inflammatory injury, involving the ipsilateral cortex and basal ganglia with massive infiltration of neutrophils, macrophages and microvascular proliferation, was exhibited in all normothermic rats. However, hypothermic MCAO rats showed minimal inflammatory response.Conclusion: The present study provides experimental evidence for the beneficial role of mild hypothermia using reversible MCAO in rats. Our results indicate that moderate hypothermia has a significant protective effect on the inflammatory injury induced by transient focal cerebral ischemia. Perhaps, the therapeutic effect was related to a reduction in releasing of cytotoxic products and improvement of the cerebral microcirculation.Bangladesh Journal of Neuroscience 2013; Vol. 29 (1) : 18-23